A randomized pilot study on self‐management in head and neck lymphedema - McLaughlin, Tess M. (Laryngoscope Investig Otolaryngol, 2020)
BACKGROUND: The purpose of this pilot trial was to determine the feasibility of a self‐managed lymphedema randomized control trial to test the effectiveness of a head and neck‐specific exercise protocol. METHODS: Nine participants were randomized to receive usual treatment provided by an Australian metropolitan teaching hospital (n = 4) or usual treatment with an added head and neck exercise regime (n = 5). Feasibility was assessed through ease of recruitment, adherence, and safety. Lymphedema reduction and quality of life (QOL) data were assessed at baseline (0 week) and follow‐up (6 weeks). RESULTS: The study was feasible in terms of safety and participant retention. However, a slow recruitment rate and low adherence may impact future trials. There were no significant differences in lymphedema reduction or QOL between groups. CONCLUSION: This pilot feasibility study demonstrated that a self‐management trial can be implemented, however, modifications will be required due to the slow recruitment and poor adherence rates. LEVEL OF EVIDENCE: 1b: Individualized randomized control trial.